2007
DOI: 10.1143/jjap.46.5879
|View full text |Cite
|
Sign up to set email alerts
|

Glycothermal Synthesis of Scheelite-Type LiEuW2O8 Nanophosphors and Their Structural Characterization

Abstract: The formation of LiEuW 2 O 8 from a tungsten source and acetates of lithium and europium(III) by autoclave treatment in 1,4butylene glycol, i.e., by a glycothermal reaction, was studied to explore a novel low-temperature wet chemical synthesis of scheelite-type tungstate compounds with WO 4 units. When dodecatungstophosphoric acid hexahydrate (DPA) was chosen as a tungsten source, a glycothermal reaction at 300 C produced crystalline scheelite-type LiEuW 2 O 8 (LEW) nanophosphors in a single phase. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…27,28 For sample DPA-2h200, the additional peak was observed in the region of 1000-1150 cm −1 , which is assigned to the vibrational modes of PO 4 units. These PO 4 units originate from the starting ingredient, DPA, 20 and the results agree with that of XRF analysis. Other peaks are assigned to alkyl chain and carboxyl groups, which are derived from the starting glycol solvents and the metal acetates.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…27,28 For sample DPA-2h200, the additional peak was observed in the region of 1000-1150 cm −1 , which is assigned to the vibrational modes of PO 4 units. These PO 4 units originate from the starting ingredient, DPA, 20 and the results agree with that of XRF analysis. Other peaks are assigned to alkyl chain and carboxyl groups, which are derived from the starting glycol solvents and the metal acetates.…”
Section: Resultssupporting
confidence: 84%
“…This would result in the acceleration of the formation of crystalline NEW. 20 Formation of crystalline scheelite-type NEW nanophosphor with the aid of phosphate groups.-Most of the diffraction peaks of sample APT-2h300P ͑Fig. 1d͒ prepared using the additional phosphorus additive, ADP, were mainly assigned as NEW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But in recent years, it has been revealed that the materials with grain size less than 100 nm exhibited different properties from conventional microcrystalline specimens [4][5][6][7]. Many kinds of luminescent materials have been prepared in nanocrystalline state by various methods [8][9][10].…”
Section: Introductionmentioning
confidence: 99%